2017
DOI: 10.1038/nn.4532
|View full text |Cite
|
Sign up to set email alerts
|

Developmental alterations in Huntington's disease neural cells and pharmacological rescue in cells and mice

Abstract: Neural cultures derived from Huntington’s disease (HD) patient-derived induced pluripotent stem cells were used for ‘omics’ analyses to identify mechanisms underlying neurodegeneration. RNA-seq analysis identified genes in glutamate and GABA signaling, axonal guidance and calcium influx whose expression was decreased in HD cultures. One-third of gene changes were in pathways regulating neuronal development and maturation. When mapped to stages of mouse striatal development, the profiles aligned with earlier em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
172
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(198 citation statements)
references
References 93 publications
(126 reference statements)
19
172
0
Order By: Relevance
“…It has been proposed that lncRNAs in the ceRNA network may be involved in the regulation of transcription. Previous studies have revealed that widespread transcriptional dysregulation occurred in HD cells and animal models, and postmortem HD brain tissues (Consortium, 2017;Hodges et al, 2006). Intriguingly, in the present study, transcripts of HAR1, which was previously shown to be down-regulated in HD patients, was also shown to be dysregulated in our study.…”
Section: Discussionsupporting
confidence: 78%
“…It has been proposed that lncRNAs in the ceRNA network may be involved in the regulation of transcription. Previous studies have revealed that widespread transcriptional dysregulation occurred in HD cells and animal models, and postmortem HD brain tissues (Consortium, 2017;Hodges et al, 2006). Intriguingly, in the present study, transcripts of HAR1, which was previously shown to be down-regulated in HD patients, was also shown to be dysregulated in our study.…”
Section: Discussionsupporting
confidence: 78%
“…These findings were unexpected as SCA3 typically presents later in life with selective neuronal vulnerability1,4,5 . The presence of disease phenotypes in undifferentiated cells could point to early developmental changes that are as yet unappreciated in SCA3, and is reminiscent of recent findings in HD, another adultonset polyQ disorder55 . Cellular properties of pluripotent stem cells, notably their heavy reliance on autophagy-dependent protein clearance and rapid rate of division, may also provide insights into polyQ expansion-driven changes in ATXN3 function.…”
mentioning
confidence: 78%
“…Next generation RNA-sequencing studies performed in HD mouse models and human HD patient induced pluripotent stem cell (iPSC)-derived or directly converted neural cultures have all highlighted dysregulation of synaptic genes. In particular, there was a downregulation of transcripts involved in the postsynaptic scaffold, neurotransmitter signaling, Ca 2+ signaling, long-term synaptic plasticity, as well as reduced transcription of neuronal activity-regulated genes (Langfelder et al, 2016;HD iPSC Consortium, 2017;Veldman and Yang, 2018;Victor et al, 2018). Importantly, these changes also hold true at the proteomic level (Langfelder et al, 2016;Hosp et al, 2017;Skotte et al, 2018).…”
Section: Insights From Systems Biology Studiesmentioning
confidence: 95%
“…In vitro co-culture systems have been useful in delineating the contribution of various afferents to SPN dysfunction (Kolodziejczyk and Raymond, 2016;Virlogeux et al, 2018). The availability of HD neural cultures either derived from iPSCs or directly converted from patients' fibroblasts (HD iPSC Consortium, 2017;Victor et al, 2018) now opens the possibility of extending such in vitro approaches to human neurons, thus providing a convenient and physiologically relevant platform for drug testing. In addition, brain organoids (Lancaster et al, 2013) and further modifications of this technique that promote establishment of functional neuronal connectivity (Giandomenico et al, 2019) offer another promising way to bring in vitro modeling of disease-related circuit impairments closer to the in vivo setting.…”
Section: Open Questions and Future Directionsmentioning
confidence: 99%